Active sites in heterogeneous ice nucleation: the example of K-rich feldspars - Kiselev, Alexei; Leisner, Thomas (Science, 2017)
From dust to ice. How does ice form on the surfaces of aerosol particles? The process is important for climate and atmospheric properties but poorly understood at the molecular level, in part because the nature of the sites where ice growth begins is unclear. Kiselev et al. used electron microscopy and computer simulations to study the deposition of aligned ice crystals on feldspar, a major component of mineral dust (see the Perspective by Murray). Surface defects of the feldspar were responsible for its high ice-nucleation efficiency. Science, this issue p. 367; see also p. 346Ice formation on aerosol particles is a process of crucial importance to Earth’s climate and the environmental sciences, but it is not understood at the molecular level. This is partly because the nature of active sites, local surface features where ice growth commences, is still unclear. Here we report direct electron-microscopic observations of deposition growth of aligned ice crystals on feldspar, an atmospherically important component of mineral dust. Our molecular-scale computer simulations indicate that this alignment arises from the preferential nucleation of prismatic crystal planes of ice on high-energy (100) surface planes of feldspar. The microscopic patches of (100) surface, exposed at surface defects such as steps, cracks, and cavities, are thought to be responsible for the high ice nucleation efficacy of potassium (K)-feldspar particles. Atmospheric ice nucleation on feldspar dust occurs at surface defects.Atmospheric ice nucleation on feldspar dust occurs at surface defects.